The knowledge of 40-60 year old women about Human Papillomavirus - Caroline Freitas Silveira; Mariana Martins de Melo; Leiner Resende Rodrigues; Bibiane Dias Miranda Parreira (Rev Rene)
This study aimed at identifying the knowledge of women between 40 to 60 years of age, about Human Papillomavirus (HPV). It is a descriptive, transversal and quantitative study done at the Center of Integral Attention to Woman’s Health in the city of Uberaba — MG, from October 2009 to January 2010, with 30 women waiting to take the Papanicolau test. The average age was of 48.7 years old. Regarding the Papanicolau test, 96.7% reported that they had already taken the test some time and 40% said that the exam avoids uterine cancer. Concerning HPV, 86.7% of the women knew the initials, but 53.3% did not know what HPV stands for. It was so concluded that these women had deficiency of knowledge about Papanicolau test and HPV. Thus, it is necessary the development of educational strategies for this specific range of age.